Una mirada descentralizada al enjuiciamiento de cárteles en el Perú - Quintana Sánchez, Eduardo (2015)
This paper analyses how IndecopI has prosecuted and sanctionedcartels within the country, taking into account whether economic agents have internalized the extent and impact of the ban of cartels and the type of reaction deployed by the authority over time.